Distribution of hydrogen peroxide over Europe during the BLUESKY aircraft campaign - Hamryszczak, Zaneta T.; Pozzer, Andrea; Obersteiner, Florian; Bohn, Birger; Steil, Benedikt; Lelieveld, Jos; Fischer, Horst (Atmospheric Chemistry and Physics, 2022)
In this work we present airborne in situ trace gas observations of hydrogen peroxide (H2O2) and the sum of organic hydroperoxides over Europe during the Chemistry of the Atmosphere – Field Experiments in Europe (CAFE-EU, also known as BLUESKY) aircraft campaign using a wet chemical monitoring system, the HYdrogen Peroxide and Higher Organic Peroxide (HYPHOP) monitor. The campaign took place in May–June 2020 over central and southern Europe with two additional flights dedicated to the North Atlantic flight corridor. Airborne measurements were performed on the High Altitude and LOng-range (HALO) research operating out of Oberpfaffenhofen (southern Germany). We report average mixing ratios for H2O2 of 0.32 ± 0.25, 0.39 ± 0.23 and 0.38 ± 0.21 ppbv in the upper and middle troposphere and the boundary layer over Europe, respectively. Vertical profiles of measured H2O2 reveal a significant decrease, in particular above the boundary layer, contrary to previous observations, most likely due to cloud scavenging and subsequent rainout of soluble species. In general, the expected inverted C-shaped vertical trend with maximum hydrogen peroxide mixing ratios at 3–7 km was not found during BLUESKY. This deviates from observations during previous airborne studies over Europe, i.e., 1.64 ± 0.83 ppbv during the HOOVER campaign and 1.67 ± 0.97 ppbv during UTOPIHAN-ACT II/III. Simulations with the global chemistry–transport model EMAC partly reproduce the strong effect of rainout loss on the vertical profile of H2O2. A sensitivity study without H2O2 scavenging performed using EMAC confirms the strong influence of clouds and precipitation scavenging on hydrogen peroxide concentrations. Differences between model simulations and observations are most likely due to difficulties in the simulation of wet scavenging processes due to the limited model resolution.